In Silico Analysis of 14-Deoxy 11, 12-Didehydro Andrographolide (AGP 2) from Sambiloto (Andrographis paniculata) as Drug Candidate Against SARS-CoV-2 - Muhammad Vicky Astria; Lud Waluyo; Roimil Latifa; Moh. Mirza Nuryadi; Rr. Eko Susetyarini; Mohd. Affendi Labo (HAYATI Journal of Biosciences, 2023)
The outbreak of the COVID-19 pandemic in the world has urged researchers to develop a vaccine or therapeutic drugs to fight this virus. This study aimed to assay 14 deoxy-11,12-didehydroandrographolide (AGP 2) ability as an inhibitor of 3-chymotrypsin like-protease (3CLPro), Papain-like protease (PLPro), and RNA-dependent RNA-polymerase (RdRp), the viral proteins of SARS-CoV-2 and to evaluate it safeness as a drug candidate. In-silico technique was performed in this study to analyze the binding interaction, complex stability between protein and ligand, and drug-likeness properties. The proteins and ligands were obtained from Protein Data Bank (PDB) and PubChem web tools, then using PyRx to identify the binding affinity score, PyMoL to visualize the 3D binding interaction, and WebGro web tools to analyze the stability of each complex. A drug-likeness evaluation was done using SwissADME, pkCSM, and Way2drug web tools. The result of this study showed that the binding affinity score for each complex is; AGP 2-3CLPro (-6.7 kcal/mol), AGP 2- PLPro (-6.4 kcal/mol), and AGP 2-RdRp (-7.0 kcal/mol) where the AGP 2-RdRp and AGP 2-3CLPro showed a stable form indicating the inhibitor ability of AGP 2. This study also demonstrates that the drug-likeness properties of AGP 2 are safe to use. Additionally, it has been proved that AGP 2 can be developed into a therapeutic drug with further studies.